Health behavior factors associated with obesity in the adult population in Croatia - Musić Milanović, Sanja (Array, 2009)
Summary: The aim of this study was to examine the association of obesity and selected health behaviors, based on the data from Croatian Adult Health Survey 2003. Cross-sectional study on representative random sample of 9070 Croatian adults showed that in both men and women, mean BMI varied significantly with age (p<0.001). It tended to increased with age until 55–64 years, and then decreased slightly in men, but remained unchanged in women. The prevalence of obesity (BMI ł 30,0 kg m–2) demonstrated almost the same prevalence in men and women, 20.1% and 20.6% respectively. The likelihood of being obese, either in men or women, was more likely in the middle-aged groups, among respondents from rural areas and those from the Continental region of Croatia, with drinking lifestyle pattern, and non-smokers. Women who mostly used animal fat for food preparations were more likely to be obese. Overweight and obesity are major public health problem in the adult population in Croatia. and health promotion strategies based on behavioral correlates are needed to prevent excess weight gain in the Croatian population